Inflammatory Indices as Markers of Vascular and Organ Involvement in Behcet's Disease - Kilic, Jehat; Yamancan, Gulsah; Dogan, Yusuf; Sahin, Sumeyye; Gunduz, Ibrahim; Alakus, Omer Faruk; Koca, Suleyman Serdar (Mdpi, 2026)
Background: Behcet's disease is a multisystem inflammatory disorder with a variable clinical course. This study evaluated the association between inflammatory indices, clinical involvement, and mortality. Methods: This retrospective study included 444 patients with BD. Clinical characteristics and laboratory data were systematically retrieved from electronic medical record system. Inflammatory indices (NLR, PLR, SII) were calculated to reflect systemic inflammation. In addition, CRP-based composite indices (IBI-NLR and IBI-SII) were derived to integrate cellular and acute-phase inflammatory responses. Disease manifestations, major organ involvement, comorbidities, and mortality were recorded to comprehensively assess disease burden and clinical outcomes. Results: In multivariable analysis, vascular involvement was associated with increased ESR level (OR = 1.013, 95% CI: 1.002-1.024, p = 0.018), and male sex (OR = 3.22, 95% CI: 1.83-5.67, p < 0.001;). ROC analysis showed the highest discriminatory performance for vascular involvement, with IBI-NLR (AUC = 0.624, p < 0.001), IBI-SII (AUC = 0.609, p = 0.001) and NLR (AUC = 0.597, p = 0.004). Moreover, NLR (AUC = 0.571, p = 0.017), IBI-NLR (AUC = 0.576, p = 0.010), and IBI-SII (AUC = 0.562, p = 0.036) had modest discrimination for major organ involvement. In contrast, inflammatory indexes were not predictive for mortality (p > 0.05 for all). Mortality was independently associated with higher creatinine (OR = 1.086, p = 0.048), higher ESR (OR = 1.023, p = 0.046), and lower uric acid levels (OR = 0.454, p = 0.002). Conclusions: Inflammatory indices may not predict mortality in BD but can help identify vascular and major organ involvement. Male sex and ESR level are associated more severe disease, while mortality is associated with renal dysfunction and systemic inflammation in BD.
Keywords: behcet's disease; & imath;nflammatory burden & imath;ndex; erythrocyte sedimentation rate; vascular involvement; mortality